Experimental Investigation of Corbel between ECC and HPFRC - Wan Adnan, Wan Norsyahida (IRC, 2019)
“Until today, a total of nearly 40,000 people lost their lives due to collapse of various structures in South East Asia as stated by the National Crime Records Bureau (NCRB). The failure in building components tend to occur depending on materials, designs, method of construction, environmental conditions and the use to which the building is put. Substandard materials and design errors such as poor joint performances between beam and columns are major causes of component failure. First engineered in the 1900’s, Hughes and Crisp (2008) stated that, corbels have proved to be ideal for supporting significant loads from beams or slabs. This paper aims to investigate the comparison between the strength of ECC Corbel and High-Performance Steel Fiber Corbel reinforced internally with steel rebar and those two types of mixture. Four specimens will be constructed and tested. Test parameters included the absence of secondary reinforcement steel rebar and the difference shear span to depth ratio, a/d. All corbels were tested under vertical and horizontal load. The results obtained from this study, together with some other available data, indicated a considerable improvement in the ultimate load-carrying capacity of corbels.”